2015
DOI: 10.1016/j.jinsphys.2015.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the wing colouration in the dragonfly Zenithoptera lanei (Odonata: Libellulidae) and its role in intraspecific communication

Abstract: Zenithoptera dragonflies are known for their remarkable bluish colouration on their wings and unique male behaviour of folding and unfolding their wings while perching. However, nothing is known about the optical properties of such colouration and its structural and functional background. In this paper, we aimed to study the relationship between the wing membrane ultrastructure, surface microstructure and colour spectra of male wings in Zenithoptera lanei and test the hypothesis that colouration functions as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…While the wings of many odonates are transparent, those of some species are conspicuously coloured. Recent studies have shown that colour formation on the wing membranes relies on pigmentation, optical interference by multilayers in the cuticle, light scattering by waxy structures, or a combination of these mechanisms [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…While the wings of many odonates are transparent, those of some species are conspicuously coloured. Recent studies have shown that colour formation on the wing membranes relies on pigmentation, optical interference by multilayers in the cuticle, light scattering by waxy structures, or a combination of these mechanisms [20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Zenithoptera lanei have extremely bright-blue-coloured wings, and therefore are often called Morpho among dragonflies (figure 1a) [25]. The present study shows for the first time that their wing membranes are supplemented with extremely fine taenidia-bearing trachea, with diameters of typical insect tracheoles (0.3-2.0 mm) [11].…”
Section: Resultsmentioning
confidence: 50%
“…Usually, cuticular wax crystals have a similar size, shape and abundance on the dorsal and ventral wing surfaces, resembling filaments and rods [24]. While Z. lanei males exhibit normal crystals on the ventral surface of the wings, they have two hierarchically organized layers of wax crystals on the dorsal surface: a lower layer of extremely long filaments and an upper layer of leaf-shaped crystals [25]. Females also exhibit thick wax coverage on the dorsal surface of the wings, but do not have such a complex hierarchical structure of wax crystals as males.…”
Section: Resultsmentioning
confidence: 99%
“…With the expansion of this design to cover a range of prey size treatments in two different colour patterns, we were also able to rule out a potential interaction between prey colour pattern and size. Colour cues are clearly used in conspecific identification and communication, since odonates exhibit a wide variety of colours and patterns that can vary intra- and inter-specifically [28, 29]. “Percher” dragonflies have specialized ommatidia on the dorsal portion of their eye which allows them to see prey against a bright sky backdrop [30].…”
Section: Discussionmentioning
confidence: 99%